Flexural behaviour of over-reinforced concrete beam using external steel plate / Shatha Sahib Kareem - Shatha Sahib , Kareem (2020)
Over-reinforced concrete beam fails by crushing of the concrete compression zone before the yielding of steel reinforcement in the tension zone. An over-reinforced concrete beam may failed suddenly without warning before failure as the failure is instantaneous. Therefore, numerous codes of practices recommended a beam design to avoid brittle failure. However, in some situations, due to the limitation of spaces, using over-reinforced concrete beam is not avoidable. Previous researches showed that it is possible to design an over-reinforced concrete beam without brittle failure using the methods such as helical-reinforcement, short-stirrups, and hybrid-system. This study is an effort to investigate the performance of a new over-reinforced concrete beam section with ductile behaviour using steel plate on the beam compression zone. For this purpose, five full scale over-reinforced concrete beams with the same cross-section and length of 200×300×2400 mm, and the same concrete compressive strength and reinforcement ratio were constructed and tested. Steel plates with the same length but different in the thicknesses i.e. 6, 10 and 15 mm were used to fully cover the compression zone (a length of 1100 mm) of the beams. The steel plates were bolted on the beams. To investigate the effect of bolting arrangement, a beam with 6 mm steel plate but bolted with different spacing was also prepared. In addition, FE modelling was developed and verified against the results of the experimental works in this study. The FE modelling was also used to study the influence of the total number, diameter, length and spacing of the bolts, thickness and length of the steel plates, as well as the types of loading on the flexural behaviour of the beams. From this parametric study, the relationship between different parameters on the flexural behaviour of over-reinforced concrete beam was also deliberated. The results showed that all the bolt-compression steel plate (BCSP) beams failed in a ductile manner in contrast with the control beam. It was revealed that BCSP-system significantly improved the beams‟ spalled load and flexural capacity over the control beam. All the BSCP concrete beams showed higher flexural strength of about 74% to 158% over the control beam with an increase of energy absorption in the range of 247.5% to 458.3%. The stiffness was also improved with an increase in thickness of steel-plate. It was also found that the FE model which included the combined stiffness‟s of concrete, reinforcing steel and cracking of the concrete can predict the behaviour of the over-reinforced concrete beams. In general, the load-deflection curve from the experiment and the FEM analysis were in good agreement. It can be concluded that using steel-plate in compression zone of an over-reinforced concrete beam is an effective and practical method in retrofitting and/or strengthening of reinforced concrete beams.